A coesão referencial em textos escritos e orais de alunos da escola básica - Pascoal, Claudiele da Silva (2020)
The importance of activities in which students practice the ability to express themselves in both written and oral language through textual genres is highlighted in the National Curriculum Parameters and the National Common Curricular Base, documents which guide education in Brazil. In this regard, the following dissertation, associated with the Letters Postgraduate Program, in the field of Linguistic Studies, in the line of research of Language in the Social Context at Federal University of Santa Maria (UFSM), aims to investigate, through action research methodology, the ability to reference in the oral and written textual production of Middle School students. The theoretical framework adopted in this research considered Bakhtin (2014), regarding language as a form of interaction; Vigotski (1998), which approaches social interactionism; Koch (2014), who addresses textual linguistics; and Gancho (2003), which focus on narrative texts. When it comes to the methodology, the action research proposed by Thiollent (1996) and Tripp (2005) was conducted within the study context. The research was developed in the second semester of 2018, within a sixth grade class of Middle School in Santa Maria/ RS, where weekly workshops in Portuguese Language classes were ministered. The corpus of this study was composed of five written texts and three oral texts produced by two students in class. The selection criteria for analyzing texts produced by students was focused on frequency in the workshops, which left us with texts from two students, totaling ten written texts and six oral texts. The corpus analysis was based on Textual Linguistics. As result, we highlight that, in our research, the action research methodology was quite valid for allowing the improvement of the skills in oral and written textual production in that class. We identified during the textual production workshops that the linguistic resources of the ellipse, the recurrent uses of the personal pronoun and defined nominal expressions were frequently used by students to promote referential cohesion. Such elements are an effective strategy for maintaining the referent throughout the written and oral texts. In addition to these elements is the case of repetition, which, in the specific case of oral texts, was also worthy of mention. Thus, it was found that, during the workshops focused specifically on cohesion, these cohesive linguistic resources were being qualified by the students, which shows that the articulated work between oral and written modalities can be an ally for improving learning and teaching.